Kejahatan Ekonomi di Balik Karhutla: Analisis Yuridis-Ekologis terhadap Praktik Alih Fungsi Hutan oleh Korporasi - sukartini sukartini (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
Forest and land fires (karhutla) in Indonesia are not only ecological events, but also a form of structured economic crime. Corporations often use burning as a cheap strategy to convert forests into plantations, particularly palm oil and industrial timber plantations. This practice causes enormous losses, including ecosystem degradation, transboundary haze, public health problems, and trillions of rupiah in economic losses borne by the state and the public. This article aims to analyze the legal framework, corporate modus operandi, and the link between forest and land fires and financial crime. The method used is normative jurisprudence supported by empirical data from court decisions, official reports, and academic literature. The results of the study show that, first, the enforcement of corporate criminal liability in forest and land fire cases is still weak due to overlapping regulations and difficulties in proving the case. Second, corporate modus operandi includes large-scale land burning, the use of third parties, permit manipulation, and strategic litigation to weaken charges. Third, forest and land fires are closely related to financial crime practices, such as permit corruption, money laundering, and cross-border illicit capital flows, which strengthen forestry crime networks. Thus, forest and land fires must be viewed as economic-ecological crimes that require regulatory reform, strengthening of technology-based surveillance, enforcement of the follow the money principle, and cross-sectoral and international cooperation. These integrated efforts are important to create effective, fair, and sustainable law enforcement.